2020
DOI: 10.1101/2020.05.11.089342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phage-DMS: a comprehensive method for fine mapping of antibody epitopes

Abstract: Understanding the antibody response is critical to developing vaccine and antibody-based therapies and has inspired the recent development of new methods to isolate antibodies. However, methods to define the antibody-antigen interactions that determine specificity or allow escape have not kept pace. We developed Phage-DMS, a method which combines two powerful approachesimmunoprecipitation of phage peptide libraries and deep mutational scanning (DMS) -to enable highthroughput fine mapping of antibody epitopes. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 38 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…24,820 unique peptides were designed in total; the peptide library included wildtype peptides that could be used to define the antibody epitope and peptides with all possible mutations to determine those within the defined epitope that disrupt or enhance antibody binding. Two biological replicate libraries of these peptide sequences were cloned as we have done previously (Garrett et al, 2020). Deep sequencing of the final duplicate libraries (Library 1 and Library 2) indicated that each contained a high percentage of all unique sequences (96.0% and 95.9%, respectively) ( Figure S1).…”
Section: Generation Of the Spike Phage-dms Librarymentioning
confidence: 99%
See 4 more Smart Citations
“…24,820 unique peptides were designed in total; the peptide library included wildtype peptides that could be used to define the antibody epitope and peptides with all possible mutations to determine those within the defined epitope that disrupt or enhance antibody binding. Two biological replicate libraries of these peptide sequences were cloned as we have done previously (Garrett et al, 2020). Deep sequencing of the final duplicate libraries (Library 1 and Library 2) indicated that each contained a high percentage of all unique sequences (96.0% and 95.9%, respectively) ( Figure S1).…”
Section: Generation Of the Spike Phage-dms Librarymentioning
confidence: 99%
“…To determine the effect of mutations on antibody binding to S protein epitopes, we compared the relative enrichment of wildtype peptides and mutant peptides within the epitopes defined above. To quantify the effect of each amino acid on binding, we calculated the differential selection of mutant peptides versus wildtype peptides and scaled this value by the strength of binding to the wildtype peptide, as we have previously done for Phage-DMS experiments; this measure is highly correlated with the relative binding of individual mutant peptides by ELISA (Garrett et al, 2020). Plotting the scaled differential selection values for all mutants at each site in a heatmap allows for the visualization of sites where mutations led to a detectable loss of binding.…”
Section: Patient-to-patient Variability In Mutations That Lead To Losmentioning
confidence: 99%
See 3 more Smart Citations